Understanding atypical eating behaviours in women with obsessive-compulsive disorder: A qualitative study - Sonay Kucukterzi-Ali; Amanda K. Ludlow; Roberto Gutierrez; Naomi A. Fineberg; Tim M. Gale (PLoS ONE, 2026)
Atypical eating behaviours in adults with obsessive-compulsive disorder (OCD) are often overlooked or misdiagnosed, possibly due to some eating difficulties being synonymous with their associated OCD. This study explored eating experiences from the perspective of eleven females with OCD, aged between 20 and 45 years. A series of semi-structured interviews were conducted and analysed using reflexive thematic analysis. Three central themes were generated from the data: the hidden burden; the importance of control; the detrimental impact of OCD on eating. These themes encapsulated how prevalent atypical eating difficulties were among the females with OCD, often emerging in response to heightened states of emotions, the need for control and/or as a reflection of their OCD symptoms. Whilst the reported eating behaviours did not always meet the diagnostic threshold for an eating disorder, participants described them as posing significant challenges to their daily functioning, as well as negatively affecting those around them. The current findings suggest that individuals with OCD often perceive their eating behaviours to be directly associated with their OC symptoms, highlighting the need to acknowledge these challenges in clinical practice. A better understanding of the broader implications of OCD, particularly on eating behaviours, is warranted to facilitate tailored interventions and prevent additional complications associated with eating behaviours in this group.